Urbanism(s) and informality(ies) in Rio de Janeiro, Brazil - Luiza Farnese Lana Sarayed-Din; Luiz Alex Silva Saraiva (Ciudades, 2024)
This article examines urbanisms and informalities intertwined with Brazilian popular culture, in the light of a theoretical and empirical study of two examples from the city of Rio de Janeiro, Brazil. The primary conclusions underscore a tension between formal urbanism, which attempts to propagate a uniform way of urban existence, and the exuberance of life in the urbe. This highlights that urbanism is inherently multifaceted and requires the incorporation of multiple urban existences within global south cities while considering their distinctions.